Starch biopolymer films containing carbon black nanoparticles: properties and active food packaging application - Othman, Siti Hajar; Zaid, Nur Syahira; Ahmad Shapi'i, Ruzanna; Nordin, Norhazirah; A. Talib, Rosnita; Mohamed Amin Tawakkal, Intan Syafinaz (Elsevier, 2025)
Developing sustainable active food packaging films is vital to address environmental concerns and prolong the food shelf life, thereby aiding the growth of the agri-food industry. This work aims to develop active food packaging films using blends of cassava starch and different concentrations of carbon black nanoparticles (CBN; 1, 2, 3, 4 %w/v). The mechanical, thermal, barrier, UV-blocking capacity, and antibacterial characteristics of the films were characterized accordingly, and the applicability of the films as active food packaging was established on cherry tomatoes. It was found that the addition of CBN in the starch films, especially at higher concentrations, enhanced the mechanical strength, thermal stability, and water vapor permeability and oxygen transmission rate. Even with 1 %w/v loading of CBN, the films were able to block around 45 % of ultraviolet-C (UV-C) light, showing the potential to serve as sustainable UV shields that can help lengthen the food shelf life. Moreover, the addition of 2 %w/v CBN in the starch films was adequate to inhibit the Staphylococcus aureus and Escherichia coli bacteria. Cherry tomatoes packaged with films containing 2 %w/v CBN exhibited the least mold growth and the lowest percentage reduction in firmness and weight, showing the potential usage for active food packaging.